PENGARUH MEDIA SOSIAL DAN FASILITAS TERHADAP KEPUTUSAN MENGINAP DI HOTEL MERLIN MAUMERE - Stefania Galathzia; Magdalena Silawati Samosir; Nunsio Handrian Meylano (Universitas Nusa Nipa Maumere, 2026)
This study aimed to: (1) determine the description of hotel booking decisions, social media, and facilities; (2) analyze the effect of social media and facilities on hotel booking decisions both partially and simultaneously. The population in this study consisted of 98 visitors to Hotel Merlin Maumere. As the population is limited, this study was conducted using a census or saturated sampling technique. Data were collected through questionnaires and were analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing was conducted through the F-test and t-test. The results of the descriptive analysis showed that the variable of hotel booking decisions was in the good category, the social media variable was in the good category, and the facilities variable were in the good category. The statistical results of the t-test showed that, partially, the social media variable had a positive and insignificant effect on hotel booking decisions. Furthermore, the facilities variable had a positive and significant effect on hotel booking decisions. Furthermore, the statistical results of the F-test showed that, simultaneously, the social media and facilities variables had a significant effect on hotel booking decisions. The results of the determination analysis showed that the two independent variables in this study were able to explain the variation in the increase and decrease of hotel booking decisions at Hotel Merlin Maumere by 24.9%. Keywords: Social Media, Facilities, Hotel Booking Decisions